Synthesis and Study of Bi2Ce2O7 as Inorganic Pigment - Těšitelová, Kateřina; Šulcová, Petra (My University, 2016)
The aim of this contribution was to obtain a new anvironmetally friendly yellow compound based on the mixed oxides Bi and Ce. The pigment with general formula Bi2Ce2O7 was synthetized by classical ceramic method. The objective was to suggest and elaborate synthesis conditions of this compound, investigate its colour possibilities and verify its applicability.
Syntéza a studium anorganického pigmentu Bi2Ce2O7
Keywords: Bismuth Mixed Oxides; Inorganic Pigments; Pyrochlore Compounds; Colour Properties; Yellow Colour; směsné oxidy na bázi bismutu; anorganické pigmenty; pyrochlorové sloučeniny; barevné vlastnosti; žlutá barva